RETRACTED: Determination of the optimal parameters of the control sensor at the crossing in the control mode - Aliev Ravshan; Aliev Marat; Khakimov Shoyatbek (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001